Conservative management of dental erosion in adolescents with medical conditions - Mohd. Nor, Hikmah; Harun, Nor Asilah (Hindawi Limited, 2018)
The prevalence of dental erosion among children and adolescents is trending higher in recent decades and is becoming a major concern. Dental erosion can be caused by either extrinsic or intrinsic acids or both. One of the established aetiological factors for dental erosion by intrinsic acid is the gastrooesophageal reflux disease. The degree of dental erosions may be influenced by any medical conditions that cause a reduction in salivary flow such as the salivary gland excision, autoimmune disease, radiation to the head and neck regions, and medications. If left untreated, the dental erosion can cause dentine hypersensitivity, loss of occlusal vertical height, and aesthetic problems. For effective management of dental erosion, the aetiology of each case must be determined, and its detection at an early stage is of prime importance. This case report illustrates the conservative management of dental erosion in two adolescent patients presented with their medical conditions and behaviour issues. The aim of the treatments was to preserve the vitality of the affected teeth. The treatments were successfully completed using a conservative approach, with the patients’ medical conditions taken into consideration.